'It's like we're locked in a box': Girls' and mothers' experiences of the police and legal system following child sexual abuse. (23rd August 2021) - Butterby, Kate; Hackett, Simon
Abstract: This article focuses on girls' and mothers' experiences of police and criminal justice system responses and the impact of investigation processes following reporting of child sexual abuse. Participants spoke of a lack of timely therapeutic provision and the subsequent role of female caregivers in providing support. Problems with criminal justice processes and the subsequent impact on families' wider lives were also discussed. Findings suggest that criminal justice processes need to be better attuned to these micro level impacts and should show more sensitivity to the overall experience of children in the aftermath of sexual abuse. Implications for practice are discussed.